Daur Ulang Sampah sebagai Solusi Kreatif Mengurangi Pencemaran Lingkungan - Kalila Masni; Nuril Iman (Journal of Community Development and Empowerment, 2026)
This community service initiative aims to enhance public awareness, knowledge, and skills in waste management through recycling activities as a creative solution to reduce environmental pollution. The primary challenges faced by partners include the high volume of household waste, low rates of waste sorting, and minimal reuse of potentially valuable materials. The implementation methods involve educational socialization, practical recycling training, group mentoring, and participatory evaluation. Socialization focused on the impact of pollution on health and the environment, waste management principles, and the economic potential of recycled products. Hands-on training was conducted by transforming inorganic waste, such as plastic and paper, into functional and aesthetic products. Mentoring aimed to strengthen program sustainability by establishing management teams and simple marketing networks. The results indicate an increase in participants' understanding of waste sorting, a shift toward more environmentally conscious attitudes, and improved skills in creating creative products. Furthermore, the volume of discarded waste decreased, and small-scale recycling-based business initiatives emerged. Participatory evaluation showed high levels of participant satisfaction and a commitment to continuing independent waste management practices. This activity proves that waste recycling not only contributes to reducing environmental pollution but also fosters creativity, community empowerment, and local economic value. This service program is recommended for replication with regional contextual adjustments to expand sustainable environmental and social impacts. The involvement of local stakeholders, schools, and village governments serves as a crucial supporting factor in strengthening the adoption of eco-friendly behaviors, integrating informal curricula, and replicating the activity model in other communities inclusively and continuously through participatory planning, regular monitoring, and ongoing capacity building for all residents.